Cognitive Orientation to Daily Occupational Performance (CO-OP) in Children with Cerebral Palsy: A Systematic Review with Meta-analysis. (March 2022) - Roostaei, Meysam; Dalvand, Hamid; Rassafiani, Mehdi; Kelly, Greg; Razi, Bahman
Background: Cognitive orientation to daily occupational performance (CO-OP) is a client-centered treatment approach that was developed in the 1990s by occupational therapists.Purpose: Exploring current evidence about the effectiveness of CO-OP on children with cerebral palsy (CP).Method: Major electronic databases were searched. A narrative synthesis of current literature and meta-analyses on randomized control trials (RCTs) were conducted on changes in occupational performance.Findings: Seven studies with 103 participants were included. Four studies were RCTs with moderate levels of evidence, and three studies had single-subject designs. Although beneficial effects of CO-OP on goal achievement and transferring learned skills were reported, meta-analyses showed that CO-OP had no significant effect on the performance (WMD = 1.52, 95% CI = −1.58 to 4.63, P  = .33) and satisfaction domains (WMD = 1.71, 95% CI = −1.14 to 4.57, P  = .24) of Canadian Occupational Performance Measure scores compared to alternative interventions.Implications: CO-OP improves occupational performance but not more than alternative interventions. Results are inconclusive due to small sample sizes and heterogeneity of alternative interventions and participants. Therefore, research with a larger number of participants with sound RCT methods is needed.